2005
DOI: 10.1021/bi051179z
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Cancer-Associated I260M Variant of DNA Polymerase β Is a Sequence-Specific Mutator

Abstract: Studies show that 30% of 189 tumors sequenced to date express variants of the polymerase beta (pol beta) protein that are not present in normal tissue. This raises the possibility that variants of pol beta might be linked to the etiology of cancer. Here, we characterize the I260M prostate-cancer-associated variant of pol beta. Ile260 is a key residue of the hydrophobic hinge that is important for the closing of the polymerase. In this study, we demonstrate that the I260M variant is a sequence context-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 28 publications
6
72
1
Order By: Relevance
“…[15][16][17] In support of this idea we demonstrated that both I260M and K289M are sequence-specific mutator mutants. 13,12 Because Pol β functions in BER, our results suggest that K289M and I260M are deficient in discriminating between the correct and incorrect dNTP as they fill the gap after excision of the damaged base. If mistakes are introduced into key growth control genes during gap filling, they could result in mutations that lead to cancer.…”
Section: Pol β β Tumor-associated Variants Are Linked To Cancer Etiologymentioning
confidence: 87%
See 1 more Smart Citation
“…[15][16][17] In support of this idea we demonstrated that both I260M and K289M are sequence-specific mutator mutants. 13,12 Because Pol β functions in BER, our results suggest that K289M and I260M are deficient in discriminating between the correct and incorrect dNTP as they fill the gap after excision of the damaged base. If mistakes are introduced into key growth control genes during gap filling, they could result in mutations that lead to cancer.…”
Section: Pol β β Tumor-associated Variants Are Linked To Cancer Etiologymentioning
confidence: 87%
“…[11][12][13] Specifically, expression of either the K289M colon or I260M prostate cancer Pol β variant in mouse fibroblasts, in the presence of endogenous wild-type Pol β, results in cellular transformation as assessed by focus formation and anchorage independent growth. [11][12][13] A mutagenic basis for the transforming activity of the Pol β variants is suggested by the findings that different clones of cells expressing these polymerases were not immediately transformed but acquired the transformed phenotype after a variable number of passages and that the transformed phenotype persisted even after the expression of the Pol β variant was extinguished. The latter finding indicates that the Pol β variants induce transformation by a "hit-and-run" mechanism in which the continued expression of the initiating event is not required to maintain the transformed state.…”
Section: Pol β β Tumor-associated Variants Are Linked To Cancer Etiologymentioning
confidence: 99%
“…(ii) DNA substrate sequence: since DNA sequence context can influence the catalytic properties (including fidelity) of a polymerase (20)(21)(22)(23)(24)(25), Pol X was reassayed using the same substrate employed by Salas. (iii) Pre-steady state vs. steady state: our previous analyses of Pol X were conducted in the pre-steady state (10), while those of Salas and coworkers were done in the steady state (14).…”
Section: Rationale Behind Fidelity Analysesmentioning
confidence: 99%
“…It has been noted that more than 30% of the tumor samples studied so far have polβ mutation (Starcevic et al, 2004;Trivedi et al, 2008). Pol β variants, K289M and I260M have functional phenotypes that could be related to the etiology of human cancer (Lang et al, 2003;Dalal et al, 2005). The Val246 variant was shown to mis-incorporate nucleotides through altered DNA positioning in the active site (Dalal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%